GABA, Glx, and GSH in the cerebellum: their role in motor performance and learning across age groups - Van Malderen, Shanti; Hehl, Melina; Verstraelen, Stefanie; Breugelmans, Robbe; Oeltzschner, Georg; Swinnen, Stephan P.; Cuypers, Koen (Frontiers in Aging Neuroscience, 2025)
IntroductionThe cerebellum is essential for motor control and learning, relying on structural and functional integrity. Age-related atrophy leads to Purkinje cell loss, but subtle neurochemical changes in GABA, Glx (glutamate + glutamine), and glutathione (GSH) may precede degeneration and contribute to motor decline.Methods25 younger (YA) and 25 older adults (OA) were included in this study. Magnetic resonance spectroscopy (MRS), using the MEGA-PRESS sequence, was used to investigate how age affects GABA, Glx and GSH levels in the right cerebellar hemisphere, and their relationship with motor performance, measured using a visuomotor bimanual tracking task (BTT).ResultsIn line with previous work YA outperformed OA on both the simple and complex task variants of the BTT. Furthermore, YA demonstrated faster short-term motor learning as compared to OA. On the metabolic level, no significant age group differences in cerebellar GABA, Glx or GSH levels, nor any task-related modulation of GABA or Glx were observed. Additionally, neither baseline neurometabolite levels nor their modulation predicted motor performance or learning.DiscussionThese results align with previous research suggesting that neurometabolic aging is region-specific, with the cerebellum potentially being more resilient due to its slower aging process. Since neither baseline nor task-related modulation of GABA, Glx, or GSH predicted motor performance or learning, cerebellar neurometabolite concentrations may not directly underlie age-related behavioral changes. Instead, volumetric decline and changes in structural and functional connectivity in the aging cerebellum may play a more significant role in motor decline as compared to neurochemical alterations. Nonetheless, it is important to consider that motor performance and learning rely on distributed brain networks—including cortical and subcortical structures—which also undergo age-related changes and may contribute to observed behavioral declines. While our findings do not support a direct role of cerebellar neurometabolite levels in age-related motor performance differences, they underscore the complexity of neurochemical aging.